P0586ACUTE KIDNEY INJURY IN PATIENTS UNDERGOING CARDIAC SURGERY: A PROSPECTIVE, OBSERVATIONAL STUDY TO ASSESS INCIDENCE, SEVERITY, RISK FACTORS AND MORTALITY IN TERTIARY CARE HOSPITAL IN INDIA. (6th June 2020) - Sharma, Reetesh; Jain, Salil; Trehan, Naresh
Abstract: Background and Aims: Acute kidney injury (AKI) occurs in up to 30% of patients undergoing cardiac surgeries and is associated with increased morbidity and mortality. There is paucity of such data in our country. Hence this study was done to assess the incidence of AKI following cardiac surgery and its associated risk factors along with outcomes, in the Indian context. The incidence and severity of AKI in patients with normal renal parameters vs those with underlying CKD was studied. We also compared incidence and severity of AKI in patients undergoing surgery off pump vs on pump. Method: All patients age>25yrs of either gender undergoing cardiac surgeries were enrolled prospectively from July to October 2018. Patients undergoing aortic surgeries or on dialysis, renal transplants or with pre-existing AKI were excluded. Incidence and severity of AKI was defined by the AKIN criteria. NKF/DOQI definition was used to define CKD. Prevalence of risk factors such as age, sex, BMI, diabetes mellitus, hypertension, dyslipidemia, CKD, CVA, peripheral vascular disease (PVD), prior myocardial infarction (MI), peri-operative acute myocardial infarction (AMI), use of cardiopulmonary bypass (CPB) and prolonged ventilation were assessed. Results: 1, 040 patients were enrolled with these baseline characteristics: 83.5% were males, mean age 58.2±10.4 years, mean BMI 25.6±4.3, diabetes in 48.2%, hypertension in 57.5%, dyslipidemia in 70%, CVA in 36%, CKD in 6.3%, PVD in 0.9%, peri-operative AMI in 0.6%, use of CPB in 24%. Overall incidence of AKI was 23.3% and was 71.2% in patients with underlying CKD. AKI was more severe in patients with higher CKD stages. Stage3 AKI occurred only in patients with CKD stage 3 and 4. Overall the need for dialysis was 1.1% and it was 4.9% in AKI group. 8.5% of patients with CKD needed dialysis as compared to 4.1% without CKD.In multivariate risk factor analysis hypertension (p=0.01), peri-operative AMI (p=0.03), prolonged ventilation (p=0.01), CVA (p=0.01) and CKD (p<0.001) were found to be significantly associated with AKI whereas diabetes (p =0.12), PVD (p=0.13), use of CPB (p=0.4), prior AMI (p=0.07) were not significant. Mean hospital stay was prolonged in those with AKI (8.33±4.06 vs 7.16±3.01 days (p<0.001)). Overall the mortality was 0.67% and it was 2.9% in AKI group. All mortalities were associated with AKI. Conclusion: Incidence of AKI (23.3%) and mortality (0.67%) in cardiac surgery patients at our centre in India is similar to other reported studies. We found that underlying CKD is the most significant risk factor for AKI in these patients in addition to hypertension, CVA, prolonged ventilation and pre-operative AMI. Use of CPB did not increase the incidence of AKI. AKI significantly increases mean hospital stay and is also associated with increased in-hospital mortality.